2015
DOI: 10.1371/journal.pgen.1005163
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of Abdominal Pigmentation in Drosophila melanogaster

Abstract: Pigmentation varies within and between species and is often adaptive. The amount of pigmentation on the abdomen of Drosophila melanogaster is a relatively simple morphological trait, which serves as a model for mapping the genetic basis of variation in complex phenotypes. Here, we assessed natural variation in female abdominal pigmentation in 175 sequenced inbred lines of the Drosophila melanogaster Genetic Reference Panel, derived from the Raleigh, NC population. We quantified the proportion of melanization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
131
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(147 citation statements)
references
References 56 publications
12
131
4
Order By: Relevance
“…Selection for both increased and decreased pigmentation in replicate populations was associated with a decrease in longevity and increase in age-specific mortality rates relative to the paired unselected, control populations that were maintained on a similar demographic culture regime. The off-selection experiment demonstrated that 100 generations of artificial selection was sufficient to effectively fix phenotypes at their respective extremes, presumably owing to the fixation or near fixation of various alleles associated with dark and light pigmentation phenotype [20,21]. The correlated phenotypic responses are not simply the product of reduction in genetic diversity or increased inbreeding in the selected populations, as the control populations were simultaneously cultured with the same reduction in population size across generations.…”
Section: Discussionmentioning
confidence: 99%
“…Selection for both increased and decreased pigmentation in replicate populations was associated with a decrease in longevity and increase in age-specific mortality rates relative to the paired unselected, control populations that were maintained on a similar demographic culture regime. The off-selection experiment demonstrated that 100 generations of artificial selection was sufficient to effectively fix phenotypes at their respective extremes, presumably owing to the fixation or near fixation of various alleles associated with dark and light pigmentation phenotype [20,21]. The correlated phenotypic responses are not simply the product of reduction in genetic diversity or increased inbreeding in the selected populations, as the control populations were simultaneously cultured with the same reduction in population size across generations.…”
Section: Discussionmentioning
confidence: 99%
“…Dembeck et al 26 assessed natural variation in female abdominal pigmentation in 175 sequenced inbred lines of the D. melanogaster Genetic Reference Panel (DGRP), derived from the Raleigh, NC population. The two most posterior abdominal segments, tergites 5 and 6 (T5, T6), were scored for the approximate percentage of the tergite colored with black or dark brown melanin.…”
Section: Introductionmentioning
confidence: 99%
“…2 The genome-wide association (GWA) studies identified 155 DNA variants in or near ( § 1 kb) 84 genes associated with the proportion of melanization on T5 (84), T6 (34), and the difference between T5 and T6 (35). 26 Several of the top variants associated with variation in pigmentation were in tan (t), ebony (e), and brica-brac1 (bab1). Mutational analyses and targeted RNAi-knockdown showed that 17 out of 28 (61%) novel candidate genes implicated by the genome-wide association study affected abdominal pigmentation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations